Long‐term cannabidiol treatment in patients with Dravet syndrome: An open‐label extension trial - Devinsky, Orrin; Nabbout, Rima; Miller, Ian; Laux, Linda; Zolnowska, Marta; Wright, Stephen; Roberts, Claire (Epilepsia (Copenhagen), 2019)
Summary Objective Add‐on cannabidiol (CBD) significantly reduced seizures associated with Dravet syndrome (DS) in a randomized, double‐blind, placebo‐controlled trial: GWPCARE1 Part B (NCT02091375). Patients who completed GWPCARE1 Part A (NCT02091206) or Part B, or a second placebo‐controlled trial, GWPCARE2 (NCT02224703), were invited to enroll in a long‐term open‐label extension trial, GWPCARE5 (NCT02224573). We present an interim analysis of the safety, efficacy, and patient‐reported outcomes from GWPCARE5. Methods Patients received a pharmaceutical formulation of highly purified CBD in oral solution (100 mg/mL), titrated from 2.5 to 20 mg/kg/d over a 2‐week period, with their existing medications. Based on response and tolerance, CBD could be reduced or increased up to 30 mg/kg/d. Results By November 2016, a total of 278 patients had completed the original randomized trials, and 264 (95%) enrolled in this open‐label extension. Median treatment duration was 274 days (range 1‐512) with a mean modal dose of 21 mg/kg/d, and patients received a median of 3 concomitant antiepileptic medications. Adverse events (AEs) occurred in 93.2% of patients and were mostly mild (36.7%) or moderate (39.0%). Commonly reported AEs were diarrhea (34.5%), pyrexia (27.3%), decreased appetite (25.4%), and somnolence (24.6%). Seventeen patients (6.4%) discontinued due to AEs. Twenty‐two of the 128 patients from GWPCARE1 (17.2%), all taking valproic acid, had liver transaminase elevations ≥3 times the upper limit of normal. In patients from GWPCARE1 Part B, the median reduction from baseline in monthly seizure frequency assessed in 12‐week periods up to week 48 ranged from 38% to 44% for convulsive seizures and 39% to 51% for total seizures. After 48 weeks of treatment, 85% of patients/caregivers reported improvement in the patient's overall condition on the Subject/Caregiver Global Impression of Change scale. Significance This trial shows that long‐term CBD treatment had an acceptable safety profile and led to sustained, clinically meaningful reductions in seizure frequency in patients with treatment‐resistant DS.